The Cultural Connectedness Scale and its Relation to Positive Mental Health among First Nations Youth - Snowshoe, Angela (Scholarship@Western, 2015)
The mental health and wellbeing of youth is one of the most urgent concerns affecting many First Nations communities across Canada. Despite a growing recognition that cultural connectedness (i.e., the extent to which an individual is integrated within his or her First Nations culture) is an important factor for promoting the mental health of First Nations youth, there remains a clear need for a conceptual model that organizes, explains, and leads to an understanding of the resiliency mechanisms underlying this construct. Study 1 involved the development of the Cultural Connectedness Scale (CCS) with a sample of 319 First Nations, Métis, and Inuit youth (M age = 15.3; 147 male, 162 female; 10 unspecified) enrolled in grades eight through 12 from urban and reserve schools in Saskatchewan and Ontario. Study 2 explored the relationships between the components of cultural connectedness and a number of mental health indicators using a brief version of the CCS with a sample of 290 participants (M age = 14.4; 140 male, 140 female, and 10 unspecified). The CCS development combined rational expert judgments and empirical data to refine the item pool to a representative set. Exploratory factor analysis (EFA) was used to examine the latent structure of the cultural connectedness items and a confirmatory factor analysis (CFA) was used to test the fit of the final 29-item EFA model. A more parsimonious version was then proposed to improve the practical utility of the CCS. The resulting 10-item Cultural Connectedness Scale – Short Version (CCS-S) supported the invariance of the major structural elements of the construct and the relationships between the CCS-S and a number of mental health indicators were examined using hierarchical multiple linear (HML) regression analyses. The results revealed that cultural connectedness was positively associated with self-efficacy, sense of self (present and future), school connectedness, and life satisfaction and, in some cases, predicted mental health above and beyond other established ...